Effect of physical activity and different exercise modalities on glycemic control in people with prediabetes: a systematic review and meta-analysis of randomized controlled trials - Bennasar-Veny, Miquel; Malih, Narges; Galmes-Panades, Aina M.; Hernandez-Bermudez, Ivonne C.; Garcia-Coll, Natalia; Ricci-Cabello, Ignacio; Yañez, Aina M. (Frontiers in Endocrinology, 2023)
Numerous studies have shown the beneficial effects of exercise on glycemic control in people with prediabetes. However, the most effective exercise modality for improving glycemic control remains unclear. We aimed to assess which exercise training modality is most effective in improving glycemic control in a population with prediabetes.We conducted searches in Pubmed/MEDLINE, EMBASE, SPORTDiscus, Web of Science, PEDro, BVS and the Cochrane Library from the inception to June 2022. Included studies reported fasting plasma glucose (FPG), glycated hemoglobin (HbA1c) and 2-hour postprandial (2hPP) levels and implemented an exercise program lasting at least 12 weeks in adults with prediabetes. We performed direct meta-analysis using a random-effects model and a network meta-analysis. Cochran's Q statistic and the inconsistency I 2 test were used to assess the heterogenicity between studies.Twenty trials were included, with 15 trials (comprising 775 participants with prediabetes) combined in the meta-analysis, and 13 in the network meta-analysis. The meta-analysis results did not show a statistically significant reduction in fasting plasma glucose (FPG) after aerobic training (AT) intervention compared to a control group (mean (95%CI) difference = -5.18 (-13.48; 3.12) mg/dL, Z=1.22, p=0.22). However, a difference of -7.25 (-13.79; -0.71) mg/dL, p=0.03, in FPG after interval training (IT) intervention was detected compared to a control group. After resistance training (RT) intervention, FPG was significantly lower -7.80 (-12.84; -2.76) mg/dL, Z=3.90, p=0.02, and HbA1c by -0.21 (-0.27; -0.16), p<0.001, compared to the control group. The impact of RT compared to no intervention on 2hPP was not statistically significant (p=0.48). The network meta-analysis did not show statistical significance. Most of the studies presented an unclear risk of bias, and low and very low-quality of evidence. According to the GRADE criteria, the strength of the body of evidence was low.Resistance training and IT had demonstrated benefits on glycemic indices, especially on FPG, in a population with prediabetes. Further studies with larger sample sizes and a more robust methodology that compare different types of exercise modalities, frequencies, and durations, are needed to establish a beneficial exercise intervention.